Tumor CD73/A2aR adenosine immunosuppressive axis and tumor‐infiltrating lymphocytes in diffuse large B‐cell lymphoma: correlations with clinicopathological characteristics and clinical outcome. Issue 5 (4th February 2019) - Wang, Xianhuo; Zhang, Tingting; Song, Zheng; Li, Linyu; Zhang, Xuhan; Liu, Jing; Liu, Xianming; Qiu, Lihua; Qian, Zhengzi; Zhou, Shiyong; Feng, Lixia; Hu, Ge; et al.
Abstract : Novel immune checkpoint blockades, including those targeting CD73 and A2aR, are being evaluated in malignancies in clinical trials. Here, we investigated the expression of CD73 and A2aR as well as tumor‐infiltrating lymphocytes (TILs), and analyzed their correlations with clinicopathological characteristics and survival in diffuse large B‐cell lymphoma (DLBCL). We found that CD73 expression on tumor cells, rather than the total protein and gene levels of CD73, was associated with survival. Patients with CD73 + /Pax‐5 + (median survival, 57.8 months; 95% CI, 46.4–69.3) experienced significantly poorer outcomes than those with CD73 − /Pax‐5 + (median survival, 73.5 months; 95% CI, 65.9–81.2). Additionally, A2aR expression on both total TILs and CD8 + TILs was correlated with survival. Patients with A2aR + TILs (median survival, 53.3 months; 95% CI, 40.6–66.0) had a significantly shorter survival time than patients with A2aR − TILs (median survival, 74.5 months; 95% CI, 67.5–81.5). Spearman's rank test showed that CD73 expression on tumor cells was positively correlated with A2aR expression on TILs ( R  = 0.395, p  = 0.001). We further found that patients could be more precisely stratified through the combination of CD73 tumor cell expression and A2aR TILs expression, and patients with CD73 + /Pax‐5 + and A2aR + TILs experienced the worst outcome. We also revealed that patients with CD73 + /Pax‐5 + and low CD8 + TILs or low absolute lymphocyte counts had unfavorable outcomes. Overall, our findings uncovered that patients with CD73 + on tumor cells as well as A2aR + on TILs or low CD8 + TILs exhibited inferior survival, supporting potential combination strategies using CD73/A2aR immunosuppressive blockades as treatment options for DLBCL patients. Abstract : What's new? The CD73/A2a adenosine receptor (A2aR) immunosuppressive axis is suspected of facilitating tumor immune escape in diffuse large B‐cell lymphoma (DLBCL), a disease in which tumor immunosuppression potentially impacts therapeutic efficacy. Here, analyses show that CD73 expression on tumor cells and A2aR expression on tumor‐infiltrating lymphocytes (TILs) are linked to reductions in DLBCL survival. Clinical outcome was especially poor among DLBCL patients who exhibited combined expression of CD73 on tumor cells and A2aR on TILs. The findings suggest that strategies to block CD73/A2aR, possibly in combination with other immune checkpoint antibodies, may be an effective therapeutic option in DLBCL.